2011
DOI: 10.1007/s10620-011-2016-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Normalization of Anti-Tissue Transglutaminase Antibody Levels Is Common in Children with Type 1 Diabetes Mellitus

Abstract: Physicians treating children with type 1 diabetes and mildly elevated anti-TTG antibody levels might consider 12-month serologic follow-up on a gluten-containing diet rather than immediate duodenal biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 38 publications
8
46
2
6
Order By: Relevance
“…The most sensitive and specific serological tests for CD include IgA antibodies against either tTG or EMA, and both IgA and IgG antibodies for DGP (14). It seems that detection of IgG isotypes of anti - tTG or anti - DGP does not augment sensitivity for CD diagnosis in the conditions with high titer IgA isotypes (15).…”
Section: Resultsmentioning
confidence: 99%
“…The most sensitive and specific serological tests for CD include IgA antibodies against either tTG or EMA, and both IgA and IgG antibodies for DGP (14). It seems that detection of IgG isotypes of anti - tTG or anti - DGP does not augment sensitivity for CD diagnosis in the conditions with high titer IgA isotypes (15).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, although the study by Barera et al (18) described a single EmA positivity, our study shows a persistent (at least twice) positivity of celiac autoimmunity and HLA typing consistent with CD predisposition. A more recent retrospective study of 738 children with T1DM reported anti-tTG antibody levels normalized in 35% of children consuming a gluten-containing diet (6).…”
Section: Discussionmentioning
confidence: 99%
“…From a medical perspective, numerous advantages may exist in screening asymptomatic patients with T1DM, including the potential of improving diabetes control and avoidance of long-term manifestations of CD (5). However, the observation that elevated levels of antitissue transglutaminase (anti-tTG) antibody may spontaneously normalize in children with diabetes, despite continued consumption of gluten (6) and the absence of symptoms in most of these patients (5), would suggest caution before starting a gluten-free diet (GFD) in a particularly delicate group of children already struggling with a complex chronic disease in whom the addition of a second limiting dietetic condition might be remarkably difficult in front of limited benefit (7).…”
mentioning
confidence: 99%
“…Analysis -There is a relationship between celiac disease and type 1 diabetes (72). The risk for type 1 diabetes is 5-to 20-fold higher in celiac patients than in the general population (73,74).…”
Section: Davis' Point -The Increase In Celiac Disease Parallels Incrementioning
confidence: 98%